Factors associated with poor use of sequential bilateral cochlear implants in young people: A preliminary audit of poor users. (November 2013) - Emond, A; Moore, M; Tjornby, C; Kentish, R
<x content-type="archive" xml:space="preserve">Abstract</x> Six cases of poor sequential bilateral cochlear implant use (partial and complete non-use) were explored through a semi-structured interview, as part of a service evaluation and development audit to improve the quality of a paediatric implant service for sequential users. Themes associated with poor use include: (1) appearance issues, (2) unrealistic expectations of both the benefits and the challenges of adjustment, (3) poor personal motivation for the implant and for engagement in rehabilitation, and (4) dislike of the sound. Feedback from young people highlighted the importance of careful counselling about their expectations of sequential implantation, outcomes and challenges, systemic support and self-directed rehabilitation.